Drawing the body in: A comic essay on trans mobility and materiality - Councilor, KC (Women's Studies in Communication, 2018)
This comic essay engages trans embodiment and temporality, representation and identity, passing, and drawing as a form of thinking. Although uncommon, comics have been established in academia as a genre worthy of literary study as well as scholarly inquiry in the broader humanities, social sciences, and the arts (Bukatman, 2012; Chute, 2010; Howard & Jackson, 2013; Cox, 2016). Recently, scholars have also studied the use of comics making as an analytical tool in qualitative research (Katz, 2013; Sousanis, 2015; Weaver-Hightower, 2013; Flowers, 2017; Henningsen, 2017; Johnson, 2018). This comic essay invites communication scholars to consider transgender embodiment and mobility through a visual medium that can illustrate complex problems of precarity, passing, and the crossing of both material and symbolic borders and boundaries. As a genre, comics allow for dense and layered information to be conveyed very quickly, and its affordances lend themselves well to portraying the tensions in and between trans and gender-nonconforming experiences. The speech bubble and the thought bubble, for example, can juxtapose in a single panel what two characters are saying to one another and what they are thinking and feeling as well as how they are interacting and communicating non-verbally. This graphic scholarship demonstrates why the unique genre of comics is particularly apt in rendering instances of microagression or passing. I argue that comics as a form enable a shift from abstract concepts back into the body, the materiality of which can get lost in academic discourse.
Keywords: Comic essay; dept.com; embodiment; mobility; transgender

Talking, thinking, drawing: Classroom exercises - Councilor, KC; Johnson, Jenell (Graphic reproduction: a comics anthology, 2018)
"A comics anthology that illustrates the complicated and multiple experiences of human reproduction and explores comics within the growing field of graphic medicine"--
Keywords: Abortion, Induced; Graphic Novels; Infertility; Maternal Health Services; Parents; Perinatal Death; Pregnancy; dept.com; psychology